2014
DOI: 10.1603/en13072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Constant Temperatures on the Biology, Life Table, and Thermal Requirements ofAganaspis pelleranoi(Hymenoptera: Figitidae), a Parasitoid ofAnastrepha fraterculus(Diptera: Tephritidae)

Abstract: Aganaspis pelleranoi (Brèthes, 1924) (Hymenoptera: Figitidae) is a koinobiont endoparasitoid of larvae of species of the genus Anastrepha and of Ceratitis capitata. It is a candidate for use as a biological control agent, as under field conditions, it may reach a parasitism rate of 62%. The objective of this study was to determine the effect of different constant temperatures on biological parameters of A. pelleranoi when parasitizing the larva of Anastrepha fraterculus (Wiedemann, 1830) (Diptera: Tephritidae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This result is similar to that obtained by Gonçalves et al. (), who reported the largest number of offspring for Aganaspis pelleranoi (Brèthes) (Hymenoptera: Figitidae) on larvae of A. fraterculus within this same temperature range. On the other hand, studies on parasitoids of fruit flies show that temperature range of 20–25°C is best suited for parasitism (Hurtrel et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is similar to that obtained by Gonçalves et al. (), who reported the largest number of offspring for Aganaspis pelleranoi (Brèthes) (Hymenoptera: Figitidae) on larvae of A. fraterculus within this same temperature range. On the other hand, studies on parasitoids of fruit flies show that temperature range of 20–25°C is best suited for parasitism (Hurtrel et al.…”
Section: Discussionsupporting
confidence: 92%
“…For Figitidae A. pelleranoi , Gonçalves et al. () observed the same effect where males and females had longer longevity at 18°C than at 25, 28 and 30°C. This possibly occurs because insects kept at high temperature constantly suffer from water loss (Denlinger and Yocum ).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, there was a reduction (sr < 0.50) at temperatures above 28°C, showing that temperature variation affects the ratio between the sexes (Damos and Savopoulou-Soultani 2012). According to these authors, the sex ratio does not change in isolation only by the temperature variation, but also by the host quality, since under the same thermal conditions, a larger number of females of Doryctobracon areolatus (Szépligeti) (Hymenoptera: Braconidae), A. pelleranoi, and D. brasiliensis are observed at temperature 25°C in larvae of A. fraterculus (Nunes et al 2011, Gonçalves et al 2014, Poncio et al 2016. The sex ratio is a limiting factor in mass rearing of parasitoids and the success in biological control programs.…”
Section: Discussionmentioning
confidence: 98%
“…Other native wasp species have been reared under laboratory conditions, such as O. bellus, D. brasiliensis (Figure 1 C), and A. pelleranoi, allowing studies on their biology, behavior, and interspecific competitiveness (Nunes et al, 2011;Gonçalves et al, 2013Gonçalves et al, , 2014Poncio et al, 2016). The obtained results are very promising for future applied work.…”
Section: Native Parasitoidsmentioning
confidence: 99%
“…Aganaspis pelleranoi (Figure 1 A) is the best wellknown native species in terms of its biology (Ovruski, 1994;Guimarães et al, 2000). A laboratory colony was established by Gonçalves et al (2013Gonçalves et al ( , 2014Gonçalves et al ( , 2016) based on bioecology. These studies showed that the wasp prefers to attack third-instar larvae of Anastrepha fraterculus (Wiedemann) due to their best emergence rate.…”
Section: Native Parasitoidsmentioning
confidence: 99%